(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article discusses the need for book therapy / bibliotherapy, reading therapy/ the introduction of broad opportunities in the learning process. Some modern bibliotherapeutic methods have also been analyzed. Reference was also made to the universally influential role of the book in the learning process, to the attribution of new functions, to the use of new opportunities, which will be useful for teachers in terms of self-education, professional development and learners, not only to love and treat the book, but from the point of view of how to make the work of communication, behavior, correction of mental disorders more effective. The study of this interesting field of art pedagogy will allow us to expand our understanding of the mastery of the teacher’s system that motivates the learner, the new functions performed by the teacher, as well as help the teacher to conduct more interesting research and studies. The aim of the research is to identify and analyze the role of bibliotherapy in the interactive learning process. The novelty of the research. The health-keeping, motivating, value-generating, self-examining value of the bibliotherapy for the learner has been studied and analyzed, as well as its decisive influence on the teacher’s self-education and self-development. Conclusions. Bibliotherapy can be a great stimulus for the learner and the teacher to organize self-centered education. Bibliotherapy is a powerful way to relieve a child’s nervous breakdown, mental and emotional experiences. It can be useful for both teacher and the learner, as well as for the development of the teacher’s pedagogical skills and for the learner’s self-awareness.